Smart technologies of the risk-management and decision-making systems in a fuzzy data environment - Yesmagambetova Marzhan; Keribayeva Talshyn; Koshekov Kairat; Belginova Saule; Alibekkyzy Karlygash; Ospanov Yerbol (Institute of Advanced Engineering and Science, 2022)
The purpose of this article is to provide a methodology for calculating and predicting the quality of solution implementation in complicated multi-parametric organizational and technological challenges with control agent uncertainty. The article's study findings are centered on the practical application of formal methods in predicting the outcomes of control and decision-making risks under the uncertainty of model agents. The proposed mathematics and simulation applications use a multi-agent strategy to handle the general problem of assessing quality control based on